Management of cardiac diseases in liver transplant recipients: Comprehensive review and multidisciplinary practice‐based recommendations. Issue 12 (22nd April 2022) - Izzy, Manhal; Fortune, Brett E.; Serper, Marina; Bhave, Nicole; deLemos, Andrew; Gallegos‐Orozco, Juan F.; Guerrero‐Miranda, Cesar; Hall, Shelley; Harinstein, Matthew E.; Karas, Maria G.; Kriss, Michael; Lim, Nicholas; et al.
Abstract : Cardiac diseases are one of the most common causes of morbidity and mortality following liver transplantation (LT). Prior studies have shown that cardiac diseases affect close to one‐third of liver transplant recipients (LTRs) long term and that their incidence has been on the rise. This rise is expected to continue as more patients with advanced age and/or non‐alcoholic steatohepatitis undergo LT. In view of the increasing disease burden, a multidisciplinary initiative was developed to critically review the existing literature (between January 1, 1990 and March 17, 2021) surrounding epidemiology, risk assessment, and risk mitigation of coronary heart disease, arrhythmia, heart failure, and valvular heart disease and formulate practice‐based recommendations accordingly. In this review, the expert panel emphasizes the importance of optimizing management of metabolic syndrome and its components in LTRs and highlights the cardioprotective potential for the newer diabetes medications (e.g., sodium glucose transporter‐2 inhibitors) in this high‐risk population. Tailoring the multidisciplinary management of cardiac diseases in LTRs to the cardiometabolic risk profile of the individual patient is critical. The review also outlines numerous knowledge gaps to pave the road for future research in this sphere with the ultimate goal of improving clinical outcomes. Abstract : This multidisciplinary effort outlines the significant burden of cardiac disease in liver transplant recipients and provides consensus, practice‐based recommendations to optimize management.